Feasibility of percutaneous transluminal angioplasty for carotid artery stenosis. Issue 3 (March 1990) - Brown, M M; Butler, P; Gibbs, J; Swash, M; Waterston, J
Abstract : Percutaneous transluminal balloon angioplasty was attempted in seven patients with internal carotid artery stenosis, including one patient who had two procedures. All had recurrent, carotid territory, neurological symptoms considered haemodynamic in origin. Six had occlusion of the contralateral internal carotid artery. Cerebral blood flow studies confirmed diminished cerebrovascular reserve in six patients studied. In five patients (six procedures) angioplasty of the stenosed internal carotid artery was carried out successfully. With two patients technical difficulty in crossing the stenosis prevented angioplasty and in one patient with bilateral stenosis the procedure was not attempted on the second side because of the severity of the stenosis. In two patients transient aphasia developed during cannulation of the carotid artery and in another a transient monoparesis developed during the procedure. Both these haemodynamic complications recovered within ten minutes. No other complications occurred. Our experience suggests that balloon angioplasty is technically feasible in the management of stenotic carotid disease associated with haemodynamic stroke. It is a technically simple procedure requiring only a brief admission to hospital. However, its general application to patients with thromboembolic carotid-territory stroke will depend on the risk/benefit ratio compared to carotid endarterectomy or to conventional medical treatment.